Serological detection of St. Louis encephalitis virus and West Nile virus in equines from Santa Fe, Argentina - Laura Tauro; Betina Marino; Luis Adrian Diaz; Eduardo Lucca; Debora Gallozo; Lorena Spinsanti; Marta Contigiani (Memorias do Instituto Oswaldo Cruz, 2012)
St. Louis encephalitis virus (SLEV) and West Nile virus (WNV) present ecological and antigenic similarities and are responsible for serious human diseases. In addition, WNV is a significant pathogen in terms of equine health. The purpose of our study was to analyse the seroprevalence of SLEV and WNV in equine sera collected in Santa Fe Province, Argentina. The seroprevalence determined using the plaque reduction neutralisation test was 12.2% for SLEV, 16.2% for WNV and 48.6% for a combination of both viruses. These results provide evidence of the co-circulation of SLEV and WNV in equines in Santa Fe.